If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6w + -7w + -27 = 38 Reorder the terms: -27 + -6w + -7w = 38 Combine like terms: -6w + -7w = -13w -27 + -13w = 38 Solving -27 + -13w = 38 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + -13w = 38 + 27 Combine like terms: -27 + 27 = 0 0 + -13w = 38 + 27 -13w = 38 + 27 Combine like terms: 38 + 27 = 65 -13w = 65 Divide each side by '-13'. w = -5 Simplifying w = -5
| (18+6)+X=5+(52-3) | | x/5+1=10 | | Y-7=-1 | | 9+X+(8+3)=26 | | 2x^3y^2/2y | | 4n-40=7(2-2n) | | 4x=-(-4x+1)-6 | | 6+X=7+(1-1) | | 308/85=d | | 308-d=85 | | D+85=308 | | y-(y+3)+3=0 | | 308-85=d | | D-85=308 | | 2y^2=6y | | -2(x+3)=9x-39 | | (x*60)/87*2 | | x*60/87*2 | | x-99=4(x+18) | | h=36/6 | | m=24/3 | | 2cos(x)=-1 | | -5x+2=6 | | 3/4(2/3x+5/7)=8/7 | | 0.33y=-7 | | y=342-2.2x | | -16=0.5s-20 | | 2m-3*.16=3 | | 10^2x/10=100 | | 3(3c-4)=15 | | 2-x/x=1/x-3-1 | | (8x)+3=59 |